2021
DOI: 10.7759/cureus.12501
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Lung Disease in Patients With Subclinical Coronavirus Infection: Are We Bracing Ourselves for Devastating Sequelae?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide. The manifestations of COVID-19 infection can range from being asymptomatic to developing severe acute respiratory distress syndrome (ARDS). Here, we present a case series of five patients who were either asymptomatic or had very mild symptoms of COVID-19 infection upon diagnosis. These patients neither required a visit to the emergency department (ED) nor did they need to be hospitalized but became symptomatic and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
7
0
4
Order By: Relevance
“…Thus, post-COVID de novo interstitial lung disease was found in a case study of five patients 92who were either asymptomatic or had very mild symptoms. These patients had symptoms of dyspnea, intermittent cough, and lingering fatigue 4–8 weeks after COVID diagnosis, consistent with the lung disease patterns observed on CT scans [ 19 ].…”
Section: Introductionsupporting
confidence: 62%
“…Thus, post-COVID de novo interstitial lung disease was found in a case study of five patients 92who were either asymptomatic or had very mild symptoms. These patients had symptoms of dyspnea, intermittent cough, and lingering fatigue 4–8 weeks after COVID diagnosis, consistent with the lung disease patterns observed on CT scans [ 19 ].…”
Section: Introductionsupporting
confidence: 62%
“…As the acute phase of the COVID-19 pandemic winds down, the chronic diseases in its aftermath have begun to emerge. For example, many survivors are suffering from a mysterious long-haul form of the disease which culminates in a fibrotic form of interstitial lung disease (post-COVID-19 ILD) (1)(2)(3)(4)(5)(6)(7)(8)(9) . The actual prevalence of post-COVID-19 ILD (henceforth, PCLD) is still emerging; early analysis indicates that more than a third of the survivors develop fibrotic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study in Italy found that patients with nonsevere manifestations displaying pulmonary opacities showed complete remission of such lesions and no fibrosis during follow-up. In contrast, Dadhwal and Surani ( 2021 ) reported 5 cases of asymptomatic or mild symptomatic COVID-19 patients who presented shortness of breath and thorax images suggestive of resolving ground-glass opacities and later developed fibrosis 4–8 weeks after diagnosis (Rogliani and others 2020 ).…”
Section: Postinfection Pf: the Case Of Covid-19mentioning
confidence: 99%